Micro electromechanical systems (MEMS) switches analog and application - Wang, Zihao (Nanyang Technological University, 2023)
Micro-electro-mechanical systems (MEMS) switches are considered as a promising alternative to traditional electronic switches due to their small size, low power consumption, and high switching speed. MEMS switches are based on the mechanical motion of a beam, which is driven by an electrostatic force. The switching characteristics of MEMS switches are determined by the geometrical parameters of the beam, such as length, width, thickness, and the airgap between cantilever beam and fixed substrate. In this dissertation, we investigate the effect of these geometrical parameters on the pull-in voltage of MEMS switches, and how they can be optimized for the next fabrication. MEMS switches are typically composed of a beam and a substrate. The beam is suspended above the substrate by a set of anchors, and can be driven to move towards the substrate by an electrostatic force. The switching pull-in voltage, which is voltage at which the electrostatic force exceeds the restoring force of the beam, are influenced by the characteristics of MEMS switches. Hence, the pull-in voltage is a function of the geometrical parameters of the beam. In this study, we used finite element method (FEM) simulations to investigate the effect of the geometrical parameters of the beam on the pull-in voltage of MEMS switches. We considered different values of the beam length, width, thickness, and the airgap between cantilever beam and fixed substrate, then calculated the pull-in voltage for each configuration. We also performed a sensitivity analysis to determine the relative importance of each parameter on the pull-in voltage. Our simulations showed that the pull-in voltage of MEMS switches decreases with increasing beam length and width, and rises with increasing airgap and thickness. The sensitivity analysis indicated that the beam length and airgap have the most significant effect on the pull-in voltage, followed by the thickness and width. The results of our study provide a useful guide for the design and optimization of MEMS switches. By controlling the geometrical parameters of the beam, it is possible to reduce the pull-in voltage of MEMS switches, and improve their switching characteristics. Our findings can be used to guide the next fabrication of MEMS switches and improve the overall performance. In the future, it would be interesting to investigate the effect of other parameters on the switching characteristics of MEMS switches, such as the material properties, temperature, and external forces. Additionally, it would be useful to experimentally validate the simulation results.